2022
DOI: 10.1021/acs.jpcc.2c07910
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Structure, Ionic Conductivity, and Electrochemical Stability of Halogen Substitution in Solid-State Ion Conductor Li3YBrxCl6–x

Abstract: Li 3 YX 6 (X = Cl, Br) materials are Li-ion conductors that can be used as solid electrolytes in all solid-state batteries. Solid electrolytes ideally have high ionic conductivity and (electro)chemical compatibility with the electrodes. It was proven that introducing Br to Li 3 YCl 6 increases ionic conductivity but, according to thermodynamic calculations, should also reduce oxidative stability. In this paper, the trade-off between ionic conductivity and electrochemical stability in Li 3 YBr x Cl 6−x halogens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 41 publications
4
14
0
Order By: Relevance
“…This paper shows that aliovalent doping does not only affect the charge carrier concentration, but can also lead to changes in the distribution of cations in the cell, affecting diffusivity on different timescales. For future studies, it would be interesting to combine this strategy with other successful strategies such as for example halogen alloying, 66 which can affect ionic conductivity due to a change in lattice parameter (bottleneck size), lattice polarizability as well as potentially the configurational entropy.…”
Section: Discussionmentioning
confidence: 99%
“…This paper shows that aliovalent doping does not only affect the charge carrier concentration, but can also lead to changes in the distribution of cations in the cell, affecting diffusivity on different timescales. For future studies, it would be interesting to combine this strategy with other successful strategies such as for example halogen alloying, 66 which can affect ionic conductivity due to a change in lattice parameter (bottleneck size), lattice polarizability as well as potentially the configurational entropy.…”
Section: Discussionmentioning
confidence: 99%
“…), all of which can also have a significant impact on the ionic conductivity. 50 Moreover, unlike the case of bromine-substituted doped Li 3 InCl 6 , 36 bromine substitution can only slightly improve the ionic conductivity within the Na 3 InCl 6−x Br x series. Previous calculation results suggest that Li 3 InCl 3 Br 3 separates into bromine-and chlorine-rich regions, and this kind of separation increases lithium-ion diffusivity at the interface.…”
Section: ■ Methodsmentioning
confidence: 99%
“…35 Additionally, for a series of compounds Li 3 YBr x Cl 6−x synthesized by comelting of the precursors, the composition Li 3 YCl 4.5 Br 1.5 (x = 1.5) crystallizes in the trigonal P3̅ m1 phase (like Li 3 YCl 6 ), while the compositions Li 3 YCl 6−x Br x with x = 3 and 4.5 crystallize in the monoclinic C2/m phase (like Li 3 YBr 6 ), and halogen mixing allows higher conductivities (a maximum of 5.4 × 10 −3 S•cm 1 at 30 °C for Li 3 YBr 4.5 Cl 1.5 ) especially compared to that of Li 3 YCl 6 (4.9 × 10 −5 S•cm −1 at 30 °C). 36 Similarly, the Li 3 InBr x Cl 6−x series of compounds synthesized by ball milling and subsequent annealing also show various ionic conductivities, which reach a maximum of 1.2 × 10 −4 S•cm 1 at x = 3. 37 A similar complex relationship between the composition and structure was also observed in a halogenmixed sodium solid solution Na 3 GdBr x I 6−x system.…”
Section: ■ Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…32 Similar effects were also observed for Na 3− x Y 1− x Zr x Cl 6 , 33 Li 3− x Er 1− x Zr x Cl 6 34 or Li 3− x Yb 1− x M x Cl 6 with M = Zr 4+ , Hf 4+ . 35,36 In Na 3 GdBr 6− x I x , 27 Li 3 YCl 6− x Br x 37 and Li 3 HoBr 6− x I x 19 it was shown that isovalent anion substitution can be used to tune the ionic conductivity and its activation energy. While in Li 3 HoBr 6− x I x an increase in iodine content led to a decrease in activation energy due to softening of the anion lattice, this is also accompanied by an increase in Li/rare earth (RE) site disorder, which led to a reduction of the ionic conductivity due to an increased electrostatic repulsion along the lithium conduction pathways.…”
Section: Introductionmentioning
confidence: 99%